Byzantine Rank Hierarchy in the 9th–11th Centuries - Kanev, Nikolay (Studia Ceranea, 2018)
The aim of the article is to present the Byzantine secular rank hierarchy of the 9th–11th centuries. During the above-mentioned period of time Byzantium knew not one but several distinct, relatively independent official hierarchical systems. All of them, however, were mutually interconnected to varying degrees and thus formed a single, pan-imperial hierarchical construct, expressed through the so-called system of palace precedence of ranks in the empire. It is this global and more general paradigm that reflects the Byzantine hierarchical model of the 9th–11th centuries; consequently, it seems fitting to refer to it as the rank hierarchy of the classical Middle Byzantine period, in the era preceding the reforms of Alexios I Komnenos (1081–1118).